Household financial contribution to the health system after Iran's Health Transformation Plan - Mohammad Khammarnia; Fatemeh Setoodehzadeh; Alireza Ansari-Moghaddam; Eshagh Barfar; Mehdi Zanganeh Baygi; Mostafa Peyvand (James Cook University, 2020)
Introduction: Iran's Health Transformation Plan (HTP) was implemented in 2014 to decrease household expenditures. The present study seeks to measure the household financial contribution to healthcare expenditures in Sistan-Baluchistan Province after the implementation of HTP. Methods: A household survey was conducted in 2017 in Sistan-Baluchistan Province. The province is the most remote and poorest in the country and this poverty has extended to most of its main health indicators as well. About 2400 households were selected as the study samples using multistage sampling. Data were collected using the World Health Survey questionnaire. The questionnaire was designed by WHO in 2003 for assessing health system performance. Two main indicators of equity in health were measured: the percentage of households facing catastrophic health expenditure (CHE) and the Fair Financial Contribution Index (FFCI). The multiple adjusted logistic regression model was used to study the likelihood of facing CHE and to calculate the adjusted odds ratios (OR) using the model coefficients. Data were then analyzed the Statistical Package for the Social Sciences. Results: The results showed that 484 (20.2%) of the households faced CHE after implementation of the HTP. The FFCI was approximately 0.7 across the province. Statistically significant relationships were observed between the chances of facing CHE and variables including place of residence (p=0.010), having members aged more than 65 years (p=0.005) and having members with disabilities and in need of care (p=0.001). There were statistically significant relationships between the chance of facing CHE and variables related to the use of health services, including the use of dental (OR=5.212), rehabilitation (OR=2.471), diagnostic and laboratory (OR=3.637), and inpatient (OR=2.511) services. Conclusion: Despite the implementation of HTP, a high percentage of the households faced CHE. The authorities should pay more attention to low-income and remote regions of the country; in addition, the HTP should financially cover outpatient healthcare services in an adequate manner.